Socioeconomic status and quality of life among older adults with hypertension in rural Shandong, China: a mediating effect of social capital - Fu, Yingjie; Zhang, Shuo; Guo, Xiaolei; Lu, Zilong; Sun, Xiaojie (Frontiers in Public Health, 2023)
Background Improving quality of life (QoL) of older adults is becoming an important global issue. However, very few studies have been focused on the relationship between socioeconomic status (SES) and QoL in the older adults with hypertension. The purpose of this study is to investigate (a) the status of QoL, and (b) the mediating effect of social capital in the relationship between SES and QoL, among rural older adults with hypertension in China.Using multistage stratified random sampling, a face-to-face questionnaire survey was conducted among rural older adults with hypertension in Shandong province of China, from June to July, 2021. Three typical measures representing SES were used: annual household income, educational level, and employment status. Individual social capital and QoL, were assessed by the Resource Generator-China Scale (RG -China), and a 34-item simplified Patient Report Outcome (PRO) specific scale for older adults with hypertension, respectively. A total of 950 rural older adults with hypertension were included in the analysis. The mediation model based on bootstrap analyses was employed to explore the relationship between SES and QoL, and the mediating role of social capital in SES-QoL nexus. Results The sampled rural older adults with hypertension had an upper-middle level of QoL, and the average score was 132.57±19.40. SES was positively correlated with both of QoL and individual social capital, individual social capital was significantly positively correlated with QoL. Controlling for socio-demographic variables, SES was still significantly associated with individual social capital (β=0.140, P<0.001), and the higher level of individual social capital, the better QoL (β=0.153, P<0.001). Individual social capital played a partially mediating role in the association between SES and QoL (indirect effect=0.021, 95% CI: 0.010~0.038), which accounted for 9.38% of the total SES and QoL 2 effect.This study provide evidence that the effect of SES on QoL was partially mediated by individual social capital among rural older adults with hypertension in China. The government should pay more attention to those rural elderly hypertension population with lower SES, and strive to reduce the negative impact of poor SES on their QoL, based on effective strategies including improving their individual social capital.